Teaching Methods, Approaches and Strategies used in EFL Classrooms in English Language Centers and Schools of Mahabad - Khadija Muhammad Abdullah (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The qualitative research goals are to investigate the EFL teaching methods, approaches and strategies which are used in English as a foreign language classes in Mahabad. Qualitative research methods, observations and interviews were administered with 8 English teachers to obtain the data from schools and English Language Centers in Mahabad. The results of the study regarding senior high schools revealed that Grammar Translation Method (GTM) and the Audio-lingual Method (ALM) were used dominantly in the English classes. Concerning English Language Centers in Mahabad, the Audiolingual Method (ALM) and the Communicative Language Teaching (CLT) were the dominant methods applied in English classes. Being compared with senior students of the high schools, the activities and strategies used in the Centers helped students to use the language and communicate and the teachers were also more friendly and adaptable. Besides, they were able to use a variety of activities. While the teachers from schools placed emphasis on rote learning of word lists and explaining grammar elaborately. New lexical and grammatical items in English were explained in Kurdish.